Helicobacter pylori: Primary Susceptibility to Clarithromycin in vitro in Nova Scotia - Linda M Best; David JM Haldane; Gregory S Bezanson; Sander JO Veldhuyzen (Canadian Journal of Gastroenterology)
Resistance to antimicrobial agents is a major determinant of the efficacy of regimens to eradicate Helicobacter pylori. Clarithromycin (CLA) has become one of the most commonly used antibiotics for treatment of H pylori infection. In this study, the rate of primary resistance to CLA in H pylori isolated from patients was determined. One hundred sixty-two strains were recovered from patients before treatment. Strains were grown and inoculated onto Mueller-Hinton agar with 7% sheep blood. CLA epsilometer gradient agar diffusion test (E test) strips were used to test for susceptibility. Appropriate control organisms were tested to validate the assay. Plates were incubated at 37°C in a microaerophilic atmosphere for up to five days. E test results were easy to interpret. Strains were considered resistant if the minimum inhibitory concentration (MIC) was 2 µg/mL or greater. Three strains were resistant (two strains with MIC 8 µg/mL and one strain with MIC 12 µg/mL), and 159 strains were sensitive (MICs ranged from less than 0.016 to 0.38 µg/mL). Ninety per cent of the strains had MICs of 0.023 µg/mL. Primary resistance was 1.8%. These susceptibility data support the use of CLA for the treatment of H pylori in the Nova Scotia population.